Analisa Usability Portal Bacaleg PKN Menggunakan Metode System Usability Scale (SUS) - Zahroh, Arumny; Kurniawati, Laela (STMIK Amik Riau, 2024)
The Portal Bacaleg PKN is a website-based application created by PT. Internusa Cipta Solusi Perdana is used by one of the political parties participating in the 2024 election to process voting data during the election period. In order to support the update and implementation of the next nomination stage, the author proposes to measure the level of usability on the Portal Bacaleg PKN at PT. Internusa Cipta Solusi Perdana so that it can be realized in the next nomination stage. Therefore, to determine the level of usability, usability testing was carried out using the System Usability Scale (SUS) method using 10 questions, resulting in a SUS score of 96.03, which means the SUS score grade is at grade A with a Very Good rating because it is above average. -The average and Acceptability measurement values include Acceptable, which means that the PKN Bacaleg Portal is accepted and suitable for use by respondents.